PENGARUH PSIKOEDUKASI TERHADAP MOTIVASI SEMBUH DAN GLUKOSA DARAH PADA PENDERITA DIABETES MELLITUS TIPE 2 DENGAN PENDEKATAN TEORI ADAPTASI ROY - Leo Yosdimyati Romli; Hariyono Hariyono (STIKES Insan Cendekia Medika Jombang, 2018)
Background: Psychoeducation is an effective way for people with diabetes mellitus in order to get good blood glucose control and increase motivation to recovery DM patient's. The purpose of this study was to analyze the effect of psychoeducation on the motivation of recovery and patient's blood glucose. Methods: This research used quasy experimental pre post test with control group design. The population of this research is all DM patient's in the area of Puskesmas Peterongan with 17 respondents of the sample for each groups. The technique of collecting sampling is purposive sampling. The variable of this research are: psychoeducation, motivation and motivation of recovery and patient's blood glucose. The way of collecting data is by using questionnaire and laboratory test. Result and analysis: The results showed that psychoeducation did not affect the motivation to recover DM patient's in either the intervention group or the control group, and blood glucose in DM patient's according to the wilcoxon test, the motivation score for intervention group (p=0,863 (p<0,05)), control group (p=0,677 (p<0,05)) and mann-whitney test (p=0,909 (p>0,05)). The second result shows that psychoeducation had an effect on blood glucose in patient's with DM in the intervention group but had no effect on the control group, according to the Wilcoxon test results, the blood glucose score for intervention group (p=0,003 (p<0,05)), control group (p=0,163 (p>0,05)) and mann-whitney test (p=0,080 (p>0,05)). Discuss and conclusion: Psychoeducation can improve blood glucose control quite well, but still needs integration with other components related to treatment and care in DM patients. Psychoeducation is not significant enough to increase the motivation to recover DM patients but with an increase in knowledge and psychology, it is hoped that they will be able to increase their motivation to support increased self-care abilities, change behavior and have activities in order to maintain glycemic control.